The case for adding eicosapentaenoic acid (icosapent ethyl) to the ABCs of cardiovascular disease prevention. Issue 1 (2nd January 2021) - Trivedi, Kamini; Le, Viet; Nelson, John R.
ABSTRACT: The high-purity eicosapentaenoic acid (EPA) prescription fish oil–derived omega-3 fatty acid (omega-3), icosapent ethyl (IPE), was recently approved by the United States Food and Drug Administration (FDA) for cardiovascular disease (CVD) prevention in high-risk patients. This approval is based on the 25% CVD event risk reduction observed with IPE in the pre-specified primary composite endpoint (cardiovascular [CV] death, nonfatal myocardial infarction, nonfatal stroke, coronary revascularization, or hospitalization for unstable angina) in the landmark Reduction of Cardiovascular Events with Icosapent Ethyl–Intervention Trial (REDUCE-IT). Notably, this reduction in CVD event risk with IPE was an incremental benefit to well-controlled low-density lipoprotein cholesterol; patients in REDUCE-IT had elevated triglyceride (TG) levels (135–499 mg/dL) and either had a history of atherosclerotic CVD or diabetes with additional CV risk factors. Given the CVD event risk reduction in REDUCE-IT, within a year following trial results, several global medical societies added IPE to their clinical guidelines. IPE is a stable, highly purified, FDA-approved prescription EPA ethyl ester. In contrast, mixed omega-3 products (docosahexaenoic acid + EPA combinations) have limited or no evidence for CVD event risk reduction, and nonprescription fish oil dietary supplements are not regulated as medicine by the FDA. We offer our perspective and rationale for why this evidence-based EPA-only formulation, IPE, should be added to the 'E' in the ABCDEF methodology for CV prevention. We provide multiple lines of evidence regarding an unmet need for CVD prevention beyond statin therapy, IPE clinical trials, IPE cost-effectiveness analyses, and proposed pleiotropic (non-lipid) mechanisms of action of EPA, as well as other relevant clinical considerations. See Figure 1 for the graphical abstract.